(untitled) (International Journal of Engineering and Computer Science, 2017)
RDH is the technique of reversible data hiding. It maintains the original image losslessly retrieved after data embedded is obtained while protecting the image content’s as confidential. In this survey paper, we studied different reversible data hiding methods. All existing methods embed data by reversibly vacating room from the encrypted images which may result into some errors on data extraction or image restoration. Also in literature survey it is shown that DE, interpolation technique, prediction and sorting, histogram modification are the generalized methods for hiding data, but these methods are implemented only in plain images. In recent past all these methods are used in encrypted images to enhanced security. All these methods have their own advantages but no single approach is feasible as well as applicable for all the case such as, data hiding, security & privacy, image recovery etc. We have analyzed that there is need of high security as well as maintaining quality of original image during transmission and exchange of image